Socio-psychological problems of modern youth and ways of their solution - Drozd, Oksana; Turkova, Liliia; Smilichenko, Yanina (My University, 2021)
У статті вивчається молодь як соціально-демографічна група, що переживає період становлення соціальної зрілості, адаптації до світу дорослих і майбутні зміни. Молодь має рухливі межі свого віку, вони залежать від соціально-економічного розвитку суспільства, рівня культури, умов життя.
Drozd, O Socio-psychological problems of modern youth and ways of their solution / O. Drozd, L. Turkova, S. Yanina // Emerging Trends in Accounting, Finance, Marketing and Human Resource Management / ed. by Amit Kumar Goel, S. Popova, L. Popova. – India : Vandana Publications, 2021. – Vol. 1. – P. 75–84.
Keywords: Youth; psychological problems of today's youth; social problems of today's youth; state youth policy; youth organizations